Edukasi Perkuatan Tanah Menggunakan Bronjong Batu - Noor Jannah; Faujian Al Rasyid; Irpan Kurniawan (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2025)
The community service report regarding education on soil reinforcement using stone gabions in Walantaka District, Kalodran Village, Serang City, aims to increase public understanding of soil reinforcement, educate on techniques for making and installing stone gabions, and encourage community participation in protecting the environment. This activity includes outreach, training and field practice that actively involves the community. The results of this activity show an increase in community knowledge about soil strengthening, the success of installing stone gabions in areas prone to erosion, and high community participation. It is hoped that this activity can continue and become an example for other regions, with recommendations for continuing educational programs on a regular basis, inviting related parties to support similar activities, and encouraging innovation in environmentally friendly soil strengthening techniques. Thank you to all parties who contributed, especially the people of Kalodran Village, I hope this activity will be beneficial for the environment and society.